Short Beak and Dwarfism Syndrome in Ducks in Poland Caused by Novel Goose Parvovirus - Anna Karolina Matczuk; Monika Chmielewska-Władyka; Magdalena Siedlecka; Karolina Julia Bednarek; Alina Wieliczko (Animals, 2020)
Short beak and dwarfism syndrome (SBDS), which was previously identified only in mule ducks, is now an emerging disease of Pekin ducks in China and Egypt. The disease is caused by the infection of ducks with a genetic variant of goose parvovirus—novel goose parvovirus (nGPV). In 2019, SBDS was observed for the first time in Poland in eight farms of Pekin ducks. Birds in the affected flock were found to show growth retardation and beak atrophy with tongue protrusions. Morbidity ranged between 15% and 40% (in one flock), while the mortality rate was 4–6%. Co-infection with duck circovirus, a known immunosuppressive agent, was observed in 85.7% of ducks. The complete coding regions of four isolates were sequenced and submitted to GenBank. The phylogenetic analysis revealed a close relationship of Polish viral sequences with the Chinese nGPV. Genomic sequence alignments showed 98.57–99.28% identity with the nGPV sequences obtained in China, and 96.42% identity with the classical GPV (cGPV; Derzsy’s disease). The rate of amino acid mutations in comparison to cGPV and Chinese nGPV was higher in the Rep protein than in the Vp1 protein. To our knowledge, this is the first report of nGPV infection in Pekin ducks in Poland and Europe. It should be emphasized that monitoring and sequencing of waterfowl parvoviruses is important for tracking the viral genetic changes that enable adaptation to new species of waterbirds.